Measuring. Monitoring. Management. Control - M.V. Sprindzuk; V.I. Bernik; A.P. Konchits (Измерение, мониторинг, управление, контроль)
Background. The emergence and importance of the research topic is substantiated by the colossal growth in the volume of accumulated and underprocessed medical information, the evolution of mathematical and algorithmic apparatus, and the need to improve existing data processing pipelines. The purpose of the work was to review and report the new classification and concepts of data interpretation proposed by the authors, as well as an experience in software development. Materials and methods. The questions of classification of software for automating the process of analyzing bioinformational data of the genomic nature and new the principles for interpreting computational experiments in genomics are discussed. Results and conclusions. As a result, the article presents a brief review of the literature on the topic of modern computational genomics, bioinformatics, mathematical biology, medical cybernetics, big data for medicine and biology, nucleic acid sequencing technologies, experience in developing pipelines for the analysis of genomic data, the new classification of software and concepts for interpreting data in this complex interdisciplinary multi-component subject area.